PENYELESAIAN KREDIT BERMASALAH MELALUI PELELANGAN AGUNAN STUDI KASUS PADA PT. BANK SUMUT CABANG UTAMA MEDAN - ELFIRA MALIANA PANE (PREMISE LAW JURNAL, 2017)
Every giving credit to a debtor, the Bank usually faces the risk of non-performing loan which can potentially cause the loss for the Bank and debtor himself. Therefore, the Bank will decide to give credit when it has really been confident and has analyzed it profoundly. The research used judicial normative and descriptive analytic method. In its implementation, obstacles usually occur, caused by debtors, creditor, and the third party. This research analyzed a case which occurred at PT Bank Sumut, Main Branch Office, Medan, about the auction winner who could not control the auction object. The Bank attempted to do consanguinity approach. When it failed, according to the prevailing regulations, the Bank suggested the auction winner to request for the execution of clearing out to the Head of the District Court by enclosing Auction Letter as the evidence of Auction Winner. Keywords: Non-Performing Loan, Mortgage Auction